2012
DOI: 10.1117/1.oe.51.3.031204
|View full text |Cite
|
Sign up to set email alerts
|

High data rate ground-to-train free-space optical communication system

Abstract: We developed a new technology that does the acquisition, stable tracking, and fast handover for free space optical links to highspeed trains. Our prototype provided a stable communication link between a train and the ground at a data rate near 1 Gb∕s with a handover time on the order of 100 ms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…We found that the maximum handover time allowed for a continuous communication service is about 50 ms [10]. In the LaserTrainComm2012 prototype [9], the handover time was in the order of 100 ms, which was longer than the maximum handover time mentioned above.…”
Section: Free-space Optical Communication Betweenmentioning
confidence: 70%
See 1 more Smart Citation
“…We found that the maximum handover time allowed for a continuous communication service is about 50 ms [10]. In the LaserTrainComm2012 prototype [9], the handover time was in the order of 100 ms, which was longer than the maximum handover time mentioned above.…”
Section: Free-space Optical Communication Betweenmentioning
confidence: 70%
“…We developed a free-space optical communication system called LaserTrainComm2012 to realize a stable high-data-rate communication between a train and the ground [9]. Laser-TrainComm2012 achieved handover time in the order of 100 milliseconds (ms) in the IP layer, but it was not short enough to serve passengers with streaming applications such as Skype.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has good performance for unmanned vehicles with no weight restrictions [ 108 , 109 , 110 , 111 , 112 , 113 ]. In the OWC system of railway, the ATP mirror-based mechanism is more commonly used, and the primary problem to be solved is the vibration caused by the train during high-speed operation [ 114 , 115 , 116 , 117 , 118 ]. In [ 119 ], the ATP mechanism of micro-electromechanical systems-based and retroreflector-based that was used in UAVs is introduced in detail.…”
Section: Unmanned Aerial Vehicles (Uav) Ground Terminal Optical Wimentioning
confidence: 99%
“…Previous works on FSO systems have provided a comprehensive theoretical study and experimental validation on G2T communications. A high data rate (1 Gbps) G2T communications was proposed in [15], where an acquisition, tracking and pointing (ATP) mechanism based on the beaconing system was used to provide stable tracking and fast handover (i.e. 100 ms) in FSO links for high‐speed trains.…”
Section: Introductionmentioning
confidence: 99%